Orbital Paraganglioma: A Systematic Review - Huang, Natalie; Rayess, Hani M.; Svider, Peter F.; Rayess, Nadim M.; Folbe, Adam; Langer, Paul D.; Eloy, Jean-Anderson; Carron, Michael (Journal of Neurological Surgery Part B: Skull Base, 2018)
Purpose The purpose of this study was to perform a systematic review of the literature on orbital paragangliomas, evaluating clinical presentation, diagnosis, management patterns, and prognosis.Methods The systematic review was conducted based on the principles described in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. PubMed, Cochrane databases, Embase, and Web of Science were searched for articles related to orbital paragangliomas. Inclusion criteria included English language articles with original reports on human subjects. Data on clinical presentation, diagnosis, treatment, and prognosis were collected.Results Twenty-seven articles met inclusion criteria (28 total patients). The mean patient age was 37.1 years (range, 3–75 years); 13 (46.4%) patients were male. The most common presenting symptoms were proptosis (89.2%), visual acuity changes (67.9%), and extraocular muscle restriction (64.2%). Lesions were most commonly intraconal (92.9%). Single modality therapy was employed in 19 patients (67.9%), including excision in 12 patients (42.9%) and exenteration in 5 patients (17.9%). Ten patients (35.7%) developed recurrence, and there was a 92.9% survival rate (mean follow-up, 29 months).Conclusion Orbital paragangliomas are rare tumors with an excellent prognosis. These lesions commonly present with proptosis, and are primarily managed surgically with simple excision, although exenteration and adjuvant radiation may be necessary for invasive tumors. This series is the largest and most comprehensive systematic review of orbital paragangliomas conducted to date.
Keywords: orbital paraganglioma; systematic review; PRISMA